Kosova'nın Türk Dernekleri ve kuruluşları = Shoqatat dhe institucionet turke ne Kosove = Udruzenja i institucije turaka na Kosovu = The Turkish assocations and organizations in Kosova (1952-2006) - Recepoğlu, Altay Suroy (Prizen)
260 s.